2008
DOI: 10.1029/2007gl032721
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope evidence for loss of water from Mars through time

Abstract: The high D/H of the Martian atmosphere (∼5–6 × terrestrial) is considered strong evidence for the loss of Martian water to space. The timing and magnitude of the loss of water from Mars can be constrained by measurements of D/H in Martian meteorites. Previous studies of Martian meteorites have shown a large range in D/H, from terrestrial values to as high as the current Martian atmosphere. Here we show that the ancient (∼4 Ga) Mars meteorite ALH84001 has a D/H 4 × terrestrial and that the young (∼0.17 Ga) Sher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 26 publications
9
120
2
Order By: Relevance
“…Some grains contain Cl amounts at the limit of detection (<50 ppm). Trace abundances of halogens in extra-terrestrial merrillites have been reported [6,12,50].…”
Section: Phosphate Compositionmentioning
confidence: 99%
“…Some grains contain Cl amounts at the limit of detection (<50 ppm). Trace abundances of halogens in extra-terrestrial merrillites have been reported [6,12,50].…”
Section: Phosphate Compositionmentioning
confidence: 99%
“…If habitable environments did exist on early Mars, they are separated from Meridiani Planum and younger intervals by late heavy bombardment (Frey, 2008), the termination of the magnetic dynamo (Lillis et al, 2008), and associated atmospheric loss (Greenwood et al, 2008;Tian et al, 2009). Tian et al (2009) (Sleep et al, 1989), with one of the last very large impacts, recorded by the ~1350 km Isidis Basin, forming at ~3.8-3.9 Ga (Frey, 2008).…”
Section: The Duration Of Aqueous Episodes On Early Mars and Implicatimentioning
confidence: 99%
“…Indeed, the main mechanism responsible for the deuterium enrichment in the Martian atmosphere is expected to be fractionation through differential escape rates of the D and H atoms, the post-decomposition products of the HDO and H 2 O molecules (Owen et al 1988). The disk-integrated estimate of the D/H ratio must be compared with its value in the past, measured in the most ancient SNC meteorites and/or in clays at the Martian surface (Greenwood et al 2008;Usui et al 2012;Mahaffy et al 2015). For a precise measurement of the present D/H ratio on Mars and in order to avoid any possible seasonal variation, D/H should be, as much as possible, integrated over an entire Martian year.…”
Section: Introductionmentioning
confidence: 99%